Non-Vitamin K Antagonist Oral Anticoagulants and Antiplatelet Therapy for Stroke Prevention in Patients With Atrial Fibrillation: A Meta-Analysis of Randomized Controlled Trials. Issue 5 (September 2016) - Kumar, Shashi; Danik, Stephan B.; Altman, Robert K.; Barrett, Conor D.; Lip, Gregory Y. H.; Chatterjee, Saurav; Roubin, Gary S.; Natale, Andrea; Danik, Jacqueline S.
Abstract : Non-vitamin K antagonist oral anticoagulants (NOACs) are frequently used to prevent stroke in patients with atrial fibrillation. These patients are often also on aspirin or other antiplatelet agents. It is possible that treatment with both NOACs and aspirin or other antiplatelet drug may be effective in decreasing stroke, but data are sparse regarding the efficacy and safety of using both agents for stroke prevention. To address these issues, data were pooled from the 4 recent randomized, controlled trials of NOACs: apixaban, rivaroxaban, dabigatran, and edoxaban, which included 42, 411 patients; 14, 148 (33.4%) were also on aspirin or other antiplatelet drug. The number of thromboembolic events among participants on NOAC and aspirin/antiplatelet was compared with the number of events in patients on NOAC alone. Bleeding rates were also compared between those on NOAC + aspirin/antiplatelet and on NOAC alone. These results were compared with thromboembolic and bleeding events in the warfarin + aspirin/antiplatelet versus warfarin alone. No greater risk for thromboembolism was seen in patients on NOACs compared with patients on both NOACs and aspirin/antiplatelet drug. In this nonrandomized comparison, there was initially a signal toward higher thromboembolic rates among NOAC users also on aspirin/antiplatelet drugs (relative risk, 1.16; 95% confidence intervals, 1.05, 1.29) when compared with NOAC alone. This likely reflected the higher CHADS2 scores of those on aspirin/antiplatelet drugs. When the analysis was limited to studies that included aspirin rather than other antiplatelet drugs, no difference was seen for thromboembolic rates comparing dual therapy to NOAC alone (relative risk, 1.02; 95% confidence intervals, 0.90, 1.15). Higher rates of bleeding were seen with aspirin/antiplatelet drug in conjunction with NOAC. In this meta-analysis and nonrandomized comparison of aspirin/antiplatelet users and nonusers also on anticoagulation, there was no additional benefit seen of anticoagulation and antiplatelet therapy for stroke prevention when compared with anticoagulation alone. There was, however, an increased risk of bleeding. Careful assessment of the indications for antiplatelet drugs in patients with atrial fibrillation who are also receiving oral anticoagulants is warranted, and future randomized comparisons are needed.